Recurrent Bacteremic Peritonitis Caused by Enterococcus cecorum in a Patient with Liver Cirrhosis - Hsueh, Po-Ren (American Society for Microbiology, 2000)
Enterococcus cecorum (formerly Streptococcus cecorum), originally isolated from poultry intestines, has rarely been encountered in human diseases. A 60-year-old man with liver cirrhosis and hepatocellular carcinoma developed peritonitis on the seventh day of his hospitalization. Cultures of one blood sample and one ascites fluid sample obtained on that day both grew E. cecorum. The patient received intravenous cefoxitin therapy and initially responded well. Unfortunately, another episode of peritonitis associated with septic shock developed 24 days after the start of treatment, and culture of one blood specimen yielded the same organism. The isolates were identified by the conventional biochemical tests, the API Rapid ID 32 Strep system, and the API ZYM system (both systems from bioMerieux, Marcy L'Etoile, France) and were further confirmed by cellular fatty acid chromatography and 16S rRNA gene partial sequencing. The identical biotype, antibiotype, and random amplified polymorphic DNA pattern of the three isolates documented the long-term persistence of this organism in the patient. To the best of our knowledge, this is the first clinical description of recurrent bacteremic peritonitis caused by E. cecorum.